2010
DOI: 10.1051/0004-6361/200912773
|View full text |Cite
|
Sign up to set email alerts
|

Constraining compactness and magnetic field geometry of X-ray pulsars from the statistics of their pulse profiles

Abstract: Context. The light curves observed from X-ray pulsars and magnetars reflect the radiation emission pattern, the geometry of the magnetic field, and the neutron star compactness. Aims. We study the statistics of X-ray pulse profiles in order to constrain the neutron star compactness and the magnetic field geometry. Methods. We collect the data for 124 X-ray pulsars, which are mainly in high-mass X-ray binary systems, and classify their pulse profiles according to the number of observed peaks seen during one spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 127 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Within these columns, shocks heat the gas, which then emits X-rays (for a detailed review of the emission mechanisms see Hickox et al 2004;Frank et al 2002). The pulse profiles can be single-peaked, doublepeaked, or even more complex depending on the accretion geometry and viewing angle (Annala & Poutanen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Within these columns, shocks heat the gas, which then emits X-rays (for a detailed review of the emission mechanisms see Hickox et al 2004;Frank et al 2002). The pulse profiles can be single-peaked, doublepeaked, or even more complex depending on the accretion geometry and viewing angle (Annala & Poutanen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the localised mass accretion onto the magnetic poles of the rotating neutron star, it is possible to detect pulses in the X-ray light curve. The pulse profiles can be single peaked, double peaked or even more complex depending on the accretion geometry and viewing angle (Annala & Poutanen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Annala & Poutanen (2010), more than 100 X-ray pulse profiles were analysed to constrain their compactness and geometry. They found that for a centred dipole, 79% should be double peaked, implying an obliquity of α < 40 • .…”
Section: Hot Spot Light-curvesmentioning
confidence: 99%